Combinatorial Green Optimization of Individual Quick Freezer for Energy Savings through Linear Programming and Decision Theory of Shrimp Processing Industry : A Mathematical Approach - Mir Iar Ali; Parthajit Bisal; Prithwiraj Jana; Soham Garu (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The nature is becoming more and more a catholic marketplace and this environment is forcing companies to take almost everything into consideration at the same time as well as low cost with high quality production. Increase flexibility is needed to remain competitive and respond to rapidly changing markets. An effective machine optimization process is very important to the success of any organization. Machine selection and optimization represents one of the most important decisions in a company to remain competitive, in this context, we try to solve the machine optimization for energy savings and machine selection for better efficiency and production. Machining optimization and selection represents one of the most important functions to be performed by the production department. The machine optimization is a multicriterion problem which includes both qualitative and quantitative factors (criteria). In order to select the best IQF (individual quick freezer), it is necessary to make a tradeoff between these tangible and intangible factors some of which may conflict. This report deals with machine-job allocation through linier programming model and machine selection through decision theory.